The Antecedents of Thriving at Work: A Meta-Analytic Review - Liu, Danping; Zhang, Siwen; Wang, Yanling; Yan, Yufei (Frontiers in psychology, 2021)
In this study, a systematic and comprehensive meta-analysis of the relationship between thriving at work and its antecedents is conducted. The antecedents in terms of the characteristics of unit contextual features, the resources produced at work, agentic work behaviors, and personality traits are illustrated according to the socially embedded model of thriving described by Spreitzer and research. Additionally, we examine possible cultural influence on the relationship between thriving and its antecedents at different levels of individualistic culture. According to 67 independent samples ( N = 28,097), our findings reveal the correlations between thriving at work and the antecedents such as those in the form of unit contextual features, the resources produced at work, agentic work behaviors, and personality traits. Furthermore, we find that individualism moderate the relationships between certain antecedents and thriving at work. Finally, we discuss the theoretical and practical implications of this study as well as the directions for future research.